Acute limb ischemia due to ONYX 34 migration during embolization of a traumatic pseudoaneurysm of the superficial femoral artery. Issue 6 (4th June 2021) - Calugi, G; Dorigo, W; Capone, A; Esposito, D; Giacomelli, E; Pratesi, C
Abstract: Pseudo-aneurysms of the arteries of the lower limbs are a possible complication of leg trauma. Complications include rupture, infection, pain and distal embolization. This is a case of a 24-year-old man hospitalized after a car accident, in which we discovered a 1-cm large pseudo-aneurysm of the right superficial femoral artery. The pseudo-aneurysm in first place was treated by the interventional-radiologist for an endovascular repair by embolization with ONYX 34, but during the procedure the copolymer embolized in the arterial axe with complete obstruction of blood-flow in the lower limb. An urgent open surgical revascularization was then attempted by our team with the result of complete patency of the femoro-popliteal axis and of the tibial vessels. Embolization with ONYX is an effective and safe method, but it is susceptible to this type of complication for larger pseudo-aneurysms, where it is required an introduction of a larger quantity of polymer.